THE MODERATION ROLE OF SAFETY LEADERSHIP IN INFLUENCING A CULTURE OF PATIENT SAFETY - Wijaya, Kalis Satya; Indrawati, Ratna; Dian, Wahyuni (International Journal of Patient Safety and Quality, 2024)
Background This research is motivated by several problems related to patient safety in central surgical installations from 2020 to 2022. The aim of this research is to empirically reveal the influence of interprofessional collaboration and the implementation of the surgical safety checklist on patient safety culture with safety leadership as a moderating variable. Methods This research is motivated by several problems related to patient safety in central surgical installations from 2020 to 2022. The aim of this research is to empirically reveal the influence of interprofessional collaboration and the implementation of the surgical safety checklist on patient safety culture with safety leadership as a moderating variable. Results The results of the three-box method analysis concluded that interprofessional collaboration, implementation of the surgical safety checklist and patient safety culture were at the medium index, and safety leadership was at the high index. Hypothesis testing proves that simultaneously interprofessional collaboration, implementation of the surgical safety checklist and safety leadership have an effect on patient safety culture with a p value of 0.000. Partially, interprofessional collaboration has an effect on patient safety culture with a t-value of 4.900, implementation of the surgical safety checklist with a t-value of 4.444, safety leadership with a t-value of 4.740. Conclusion The moderation test concluded that safety leadership did not moderate the influence of interprofessional collaboration on patient safety culture with a t-value of 1.175, but moderated the influence of the implementation of the surgical safety checklist on patient safety culture with a t-value of 2.739.